اتجاهات تدريسيي كلية التربية للعلوم الانسانية نحو استعمال التقنيات التعليمية الحديثة في التدريس - عبيدان سلمان الجراح ا.م.د عدي; بشير حسن علي م.م. دعاء (Journal of College of Education, 2021)
The research aims to identify: (Tdrisie College of Education for Humanities attitudes towards the use of modern educational technologies in teaching). To achieve this, the researchers chose a sample of (115) pedagogy and teaching of Education for Human Sciences / University of Karbala. To measure faculty attitudes towards the use of modern educational technology in teaching at the faculty was composed of (30) items with three alternatives preparing an "I agree, I agree somewhat, I do not agree", and check the researchers of the test and persistence of sincerity, and the clarity of its paragraphs, and the time required for performing. Using the test Altaia for one sample, resulting in Search for : The presence of a high level of positive trends when Tdrisie College of Education for Human Sciences about the use of modern educational technologies in teaching. In light of the search results, the researchers recommended a set of recommendations for the actors animate the relationship research. He proposed the preparation of subsequent studies in the same field as an extension of his research, and complement him.